2005
DOI: 10.1124/jpet.105.089748
|View full text |Cite
|
Sign up to set email alerts
|

Methyllycaconitine Prevents Methamphetamine-Induced Effects in Mouse Striatum: Involvement of α7 Nicotinic Receptors

Abstract: In a previous study, we demonstrated that in rat striatal synaptosomes, methamphetamine (METH)-induced reactive oxygen species (ROS) production was prevented by methyllycaconitine (MLA), a specific antagonist of ␣7 neuronal nicotinic acetylcholine receptors (␣7 nAChR). The aim of this study was to test the influence of MLA on acute METH effects and neurotoxicity in mice, using both in vivo and in vitro models. MLA inhibited METH-induced climbing behavior by 50%. Acute effects after 30-min preincubation with 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 35 publications
3
44
0
Order By: Relevance
“…Thus, the reactive microgliosis observed presently appears to reflect the effect of METH alone on the human brain. This conclusion is consistent with the preclinical data on the use of METH in rodents (Ladenheim et al, 2000;Escubedo et al, 2005). This idea is also supported by the fact that injection of the drug in mice that mimic recreational dose regimen (4 times ϫ 2 mg/kg injections per day given for a total of 3 d) also caused significant increases in activated microglia in the mouse brain (Thomas and Kuhn, 2005a).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, the reactive microgliosis observed presently appears to reflect the effect of METH alone on the human brain. This conclusion is consistent with the preclinical data on the use of METH in rodents (Ladenheim et al, 2000;Escubedo et al, 2005). This idea is also supported by the fact that injection of the drug in mice that mimic recreational dose regimen (4 times ϫ 2 mg/kg injections per day given for a total of 3 d) also caused significant increases in activated microglia in the mouse brain (Thomas and Kuhn, 2005a).…”
Section: Discussionsupporting
confidence: 79%
“…Methamphetamine (METH) administration induces stereotypic movements in laboratory rats and mice [15,21]. In the present study, METH-induced stereotypy was observed in all animals administrated with METH.…”
Section: Discussionmentioning
confidence: 58%
“…In this study, Kolaviron (KV) was seen to delay the onset of stereotypy induced by METH. This may be due to its antioxidant properties as METH has been shown to induce neurotoxity and subsequent behavioural effects by the generation of reactive oxygen species (ROS) from the increased extracellular dopamine [15,21,23]. A study has shown that (-)-Epigallocatethin-3-O-gallate (EGCG), a powerful antioxidant and the most abundant polyphenol/flavonoid in green tea, inhibits stereotypy following low dose of METH, cocaine and caffeine [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations